Trimethoprim‐induced drug reaction with eosinophilia and systemic symptoms (DRESS) associated with reactivation of human herpes virus‐6 (HHV‐6) leading to acute liver failure - Mohsan Subhani; Victor Dong; Aveen Connolly; Jonathan Salisbury; Rosa Miquel; Sarah Walsh; Tasneem Pirani (Clinical Case Reports, 2020)
Abstract Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome can have insidious symptoms which may lead to acute liver failure and death. Prompt recognition, stopping offending drug, and initiating corticosteroid are the mainstay of treatment. Early involvement of a specialist liver unit is vital.